Frederic Adrian Delano papers - Delano, Frederic Adrian, 1863-1953.
Correspondence, writings, and other papers of Frederic Adrian Delano, deputy director general of transportation for the American Expeditionary Forces in France, relating to chiefly to the transportation of troops. Also includes material reflecting Delano's interest in the metric system.
Army officer and railroad officer.
Collection material in English.
Keywords: United States. -- Army. -- American Expeditionary Forces; Metric system; World War, 1914-1918 -- Transportation -- France; Army officers; Railroad officials